Um estudo sobre a língua e ensino do português, partindo da intolerância linguística do século XVIII - Valle, Rosemeire Stoian de Brito (2009)
This research on Historiography Linguistics area aims at the Linguistic Intolerance theme to contribute for reflection on Portuguese language teaching. To develop our studies we focused as general objective: to contribute with the Portuguese language teaching as of the exhibition of the first linguistic intolerance act in Brazil and specifics objectives are : to identify how the linguistic intolerance happened in Brazil, in the eighteenth century, to show how important it is to understand how was the politics of language in Brazil, in the colonial period; to understand the way language was taught when the Portuguese language was established as the nation language and compare the teaching proposal on eighteenth century with the present one so as to understand whether the theme Linguistic Intolerance is or is not present in different centuries. The research takes into consideration the first document, Diretório dos Indios, which clearly shows the first act of linguistic intolerance and the redirection of the Portuguese language with politics and economic objectives . It was the result of Such fact resulted in the re-directioning of one language and in the rupture of a form of teaching , which consolidated the linguistic hegemony